2018
DOI: 10.1111/dom.13483
|View full text |Cite
|
Sign up to set email alerts
|

3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid (CMPF) prevents high fat diet‐induced insulin resistance via maintenance of hepatic lipid homeostasis

Abstract: CMPF is a potential driver of hepatic lipid metabolism, preventing diet-induced hepatic lipid deposition and insulin resistance in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(102 reference statements)
2
12
0
Order By: Relevance
“…The present data show a divergent association, as we know that the serum HDL-c levels are often negatively related to TG levels, and CMPF was independently negatively associated with HDL-c and triglycerides. However, the present results were consistent with another study showing that CMPF treatment reduced circulating TG and HDL-c levels in mice 23 . The negative relationships of CMPF levels with both HDL-c and TG levels were not in conflict, since the different transcription factors and rate-limiting enzyme were affected by CMPF in TG or cholesterol biosynthesis 23 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present data show a divergent association, as we know that the serum HDL-c levels are often negatively related to TG levels, and CMPF was independently negatively associated with HDL-c and triglycerides. However, the present results were consistent with another study showing that CMPF treatment reduced circulating TG and HDL-c levels in mice 23 . The negative relationships of CMPF levels with both HDL-c and TG levels were not in conflict, since the different transcription factors and rate-limiting enzyme were affected by CMPF in TG or cholesterol biosynthesis 23 .…”
Section: Discussionsupporting
confidence: 94%
“…However, the present results were consistent with another study showing that CMPF treatment reduced circulating TG and HDL-c levels in mice 23 . The negative relationships of CMPF levels with both HDL-c and TG levels were not in conflict, since the different transcription factors and rate-limiting enzyme were affected by CMPF in TG or cholesterol biosynthesis 23 . A study showed that a high baseline log (TG)/HDL-C ratio predicts fast progression of islet bcell dysfunction 24 , so the negative association between CMPF and HDL-c might be an explanation for elevated CMPF levels in type 2 diabetes mellitus patients.…”
Section: Discussionsupporting
confidence: 94%
“…An OGTT and an intraperitoneal insulin tolerance test (IPITT) were performed as described previously ( Liu et al., 2016 ; Mohan et al., 2019 ; Prentice et al., 2014 ). Following a 15 hr overnight fast, an OGTT was performed in which mice were orally gavaged with glucose (Cat# 50-99-7, Sigma Aldrich) at 2g/kg and glucose levels were measured for 2 hr at time points 0, 10, 20, 30, 60, 90 and 120 min using a glucometer (Bayer Contour NEXT ONE Glucose meter, Ascensia Diabetes Care, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in vitro FuFAs modulate lipid metabolism in adipose tissues (Lengler et al, 2012;Lauvai et al, 2019). The 3-carboxy-4methyl-5-propyl-2-furanpropanoic acid (CMPF), a degradation product of FuFAs, also derived from the metabolism of n-3 PUFAs, could prevent or even reverse hepatic steatosis (Prentice et al, 2018;Dai et al, 2019;Mohan et al, 2019). Alvarado et al recently published a comprehensive review on FuFAs (Alvarado et al, 2021).…”
Section: Health Effectsmentioning
confidence: 99%